Synthesis and Characterization of Bis‐1, 2, 3‐Triazole Ligand and its Corresponding Copper Complex for the Development of Electrochemical Affinity Biosensors. Issue 37 (19th May 2021) - Kanso, Hussein; Ben Jrad, Amani; Inguimbert, Nicolas; Rammal, Wassim; Philouze, Christian; Thomas, Fabrice; Noguer, Thierry; Calas‐Blanchard, Carole
Abstract: The bis‐triazole ligand and its corresponding copper complexes were synthesized and characterized for the first time and proposed as new labels for the development of electrochemical aptasensors. The bis‐triazole ligand was prepared from methyl 1, 6‐heptadiyne‐4‐carboxylate and 2‐(azidomethyl)phenol using classical CuAAC in presence of different copper salts. The X‐ray structure of bis‐triazole showed a symmetry center (C1). UV‐Vis and X‐band EPR spectra showed that the coordination capacity of the bis‐triazole ligand was improved in the presence of triethylamine due to deprotonation of the triazole and phenolate moieties. After complexation with copper, the obtained complex was successfully attached to an anti‐estradiol aptamer through thiol‐maleimide coupling, and the resulting labelled aptamer was immobilized on a carbon screen‐printed electrode by carbodiimide coupling. The electrochemical response of the resulting sensor was shown to decrease in the presence of estradiol, demonstrating that the developed complexes can be applied for the development of aptasensors. Abstract : A powerful alternative for biomolecule labelling, based on the electrochemical properties of a metallic complex, is presented. A bis‐triazole ligand and its corresponding copper complex were synthesized and characterized. The coupling of the copper complex with an aptamer was realized and confirmed by mass spectroscopy analysis. The labelled aptamer was then immobilized on a screen‐printed carbon electrode for the design of an estradiol aptasensor.